DILEMA DAN PERKEMBANGAN ANTI-SLAPP DI INDONESIA: IMPLIKASI PERMA 1/2023 DAN KOMPARASI DENGAN NEGARA LAIN - Simandjuntak, Jody; Gomulia, Arauna Bianca; Riyadi, Falindevrie Yusuf; Zebua, Gladys Jennifer Nadila; Hartawan, Yolanda Amorita Virginia (Legislatif, 2024)
Strategic Lawsuit Against Public Participation (SLAPP) phenomenon is becoming increasingly prevalent in Indonesia, threatening the critical voices of the public, activists, and journalists. Indonesia has taken measures to combat SLAPP through Article 66 of Law Number 32 of 2009 (UUPPLH) and Supreme Court Regulation Number 1 of 2023 (Perma 1/2023). Nevertheless, these regulations are not yet comprehensive compared to those in countries like the United States and Canada, which have clearer and broader definitions and procedures. This study uses a normative juridical method with legislative, comparative, and conceptual approaches to examine Anti Eco-SLAPP regulations in Indonesia and compare them with those in other countries. The results indicate that although Perma 1/2023 strengthens legal protection against SLAPP, there are still weaknesses, such as unclear mechanisms for compensation and the burden of proof. Comparative studies show that Anti-SLAPP regulations in the United States and Canada offer more comprehensive protection and more effective legal procedures to prevent SLAPP. The study concludes that despite significant progress with Perma 1/2023, Indonesia needs to adopt clearer definitions and stronger procedures for legal protection against SLAPP, learning from practices in other countries to more effectively protect public participation rights.